Retrospective review of abdominal aortic aneurysm deaths in New Zealand: what proportion of deaths is potentially preventable by a screening programme in the contemporary setting?. Issue 7 (30th July 2019) - Chan, Wing Cheuk; Papaconstantinou, Dean; Winnard, Doone; Jackson, Gary
Abstract : Objectives: To describe the proportions of people dying from abdominal aortic aneurysm (AAA) who might have benefited from a formal screening programme for AAA. Design: Retrospective cross-sectional review of deaths. Setting and study populations: All AAA deaths registered in New Zealand from 2010 to 2014 in the absence of a national AAA screening programme. Main outcome measures: Known history of AAA prior to the acute event leading to AAA death, prognosis limiting comorbidities, history of prior abdominal imaging and a validated multimorbidity measure (M3-index scores). Results: 1094 AAA deaths were registered in the 5 years between 2010 and 2014 in New Zealand. Prior to the acute AAA event resulting in death, 31.3% of the cohort had a known AAA diagnosis, and 10.9% had a previous AAA procedure. On average, the AAA diagnosis was known 3.7 years prior to death. At least 77% of the people dying from AAA also had one or more other prognosis limiting diagnosis. The hazard of 1-year mortality associated with the non-AAA related comorbidities for the AAA cohort aged 65 or above were 1.5–2.6 times higher than to the age matched general population based on M3-index scores. In 2014, overall AAA deaths accounted for only 0.7% of total deaths, and 1.0% of deaths among men aged 65 or above in New Zealand. At most, 20% of people dying from AAA in New Zealand between 2010 and 2014 might have had the potential to derive full benefit from a screening programme. About 51% of cases would have derived no or very limited benefit from a screening programme. Conclusion: Falling AAA mortality, and high prevalence of competing comorbidities and/or prior AAA diagnosis and procedure raises the question about the likely value of a national AAA screening programme in a country such as New Zealand.